Cyber Open Source Intelligence in Counter-Terrorism: A Systematic Literature Review and Indonesian Case Study Analysis - Rizal Amrullah; Vedaniar Zahra Danardini Mulia (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2026)
The burden on Indonesia’s counterterrorism (CT) services has increased due to terrorist groups’ exploitation of the internet. Between 2023 and 2025, the National Counter-Terrorism Agency (BNPT) recorded 137 actors who were actively abusing the internet for terrorism; in 2025 alone, 21,199 radical content pieces were reported on key platforms. In this setting, open source intelligence (OSINT), or intelligence drawn from publicly accessible material, has become a crucial strategic weapon; nevertheless, Indonesian scholarship is still dispersed and policy-disconnected. In accordance with PRISMA 2020 principles, a systematic literature review (SLR) of 47 peer-reviewed papers (2014–2025) is presented in this work together with a case study analysis of the 2018 Surabaya bombings and the 2024 disintegration of Jemaah Islamiyah (JI). The research reveals six theme clusters: the growth of OSINT, cyber tools and AI integration, terrorist cyberspace exploitation, OSINT applications in CT, ethical-legal frameworks, and the Indonesian institutional environment. As a result of inter-agency fragmentation across Densus 88, BNPT, BSSN, and BIN, the case studies show that pre-attack OSINT signals in 2018 were observable but not put together into actionable intelligence. The study makes the case that Indonesia needs a federated OSINT doctrine that is in line with Law No. 5/2018 and the Personal Data Protection Law (UU PDP 27/2022). It also suggests a five-part policy framework based on securitization theory, intelligence cycle theory, and second-generation OSINT.